Engineering Design with SOLIDWORKS 2020 - David, C. Planchard (SDC Publications, 2019)
Engineering Design with SOLIDWORKS 2020 is written to assist students, designers, engineers and professionals. The book provides a solid foundation in SOLIDWORKS by utilizing projects with step-by-step instructions for the beginner to intermediate SOLIDWORKS user featuring machined, plastic and sheet metal components.